The relation of learning disabilities to the long-term outcomes of concussion. (January 2022) - Sicard, Veronik; Moore, Robert Davis
Abstract: Objective: This study sought to cross-sectionally evaluate the relation between learning disorders (LD) and long-term concussion outcomes. Method: Seventy-three asymptomatic male university athletes (23 history of concussion with LD; 24 history of concussion no LD; 26 controls) completed the Beck Depression Inventory-2 (BDI-II), the Profile of Mood States (POMS), the Cogstate battery, and an Oddball task during which event-related brain potentials were recorded. Results: Concussed athletes with LD exhibited greater depressive symptoms (BDI-II), greater total mood disturbance (POMS), decreased accuracy on the One-Card Learning and the N -back task (Cogstate), decreased accuracy on the Oddball task, and reduced ERN amplitude relative to both the concussed athletes without a LD and controls. Concussed athletes with LD also exhibited prolonged P3 latency relative to controls. Irrespective of LD, concussed athletes exhibited increased anger-hostility and decreased Pe amplitudes relative to controls. No differences were observed in P3a amplitude or latency. Conclusion: Having LD may be a significant factor moderating the neurophysiological, cognitive and psycho-affective outcomes of concussion, and may explain a significant portion of the persistent deficits observed by researchers and clinicians. Highlights: Identifying factors that lead to prolonged impairment is essential for advancing the scientific understanding and clinical management of concussion. Athletes with a history of concussion and a learning disability exhibited distinct deficits in psycho-affective, cognitive, and neurophysiological domains relative to teammate controls. All athletes with a history of concussion exhibited increased anger-hostility and decreased ability to consciously detect their errors relative to their teammates without a history of concussion. Having a learning disability may be a significant factor moderating the long-term outcomes of concussion.